Double burden of malnutrition and its socio-demographic determinants among children and adolescents in Malaysia: National Health And Morbidity Survey 2019 - Wai Kent Lai; Lalitha Palaniveloo; Syafinaz Mohd Sallehuddin; Shubash Shander Ganapathy (BMC, 2024)
Abstract Introduction Malaysia faces the threat of a double burden of malnutrition where undernutrition and overweight (including obesity) coexist in the same population. This study aimed to determine the anthropometric assessment among children and adolescents aged 5 to 17 years and its association with socio-demographic factors. Methods Data were extracted from the National Health and Morbidity Survey conducted in 2019. This cross-sectional survey applied a two-stage stratified sampling design. Socio-demographic characteristics were obtained. Weight and height were measured, age- and sex-specific standard scores for height and BMI were calculated to establish individual's anthropometric assessment. Having either stunting or thinness was considered undernutrition, while being overweight (including obesity) was considered overnutrition. If someone had undernutrition and/or overnutrition, they were classified as having malnutrition. The prevalence was determined using complex sampling analysis, while the association was assessed through logistic regression. The analysis included a total of 3,185 respondents. Results The prevalence of stunting, thinness, overweight and obesity among the respondents aged 5 to 17 years was 12.7%, 10.0%, 15.0% and 14.8%, respectively. The overall prevalence of malnutrition was 48.3%. Respondents residing in rural had 1.35 times more likelihood of experiencing undernutrition [AOR = 1.35, 95% CI (1.04, 1.77)] compared to their urban counterparts. Boys exhibited a greater likelihood of being overweight and obese than girls [AOR = 1.40, 95% CI (1.13, 1.73)]. Respondents aged 10 to 14 years were 1.37 times more likely to be overnutrition than those aged 5 to 9 years old [AOR = 1.37, 95% CI (1.09, 1.73)]. Conclusion There is growing evidence of the increasing prevalence of coexistence of undernutrition along with overweight and obesity among children and adolescents in Malaysia. Moving forward, greater initiatives and efforts are required to formulate strategies for planning and implementing programs and policies to expedite progress in improving nutrition.